(untitled) - Cyprich, Ondrej; Liscak, Stefan (Doprava a spoje, 2010)
The paper deals with possibilities of increasing the statistical significance level of multiple regression model of passengers demand. Topic was solved by using multivariate autoregressive (AR) models of its residuals. Two possible approaches of solving the defined problem were proposed, described and worked out in the paper.